The Influence of the Work Environment, Work Discipline on the Spirit of Work and Its Impact on Employee Performance at the Dharmasraya District Health Office - Khamri, Aprial; Heryanto, Heryanto (Archives of Business Research, 2019)
This study tries to test the effect of work environment, work discipline and work spirit on employee performance at Dharmasraya District Health Office. This study uses descriptive quantitative methods. The study population consisted of 52 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is linear regression analysis, t test, f test, determination coefficient, and path analysis using the SPSS program, with α = 0.05. The results showed that the Work Environment and Work Discipline had a partially significant effect on the Work Spirit of the Dharmasraya District Health Office Staff. Work Spirit, Work Environment and Work Discipline partially have a significant effect on the Employee Performance of the Dharmasraya District Health Office. Work Spirit as an intervening variable has a significant effect between Work Environment and Work Discipline on the performance and performance of the Health Office Staff in Dharmasraya Regency. The empirical findings indicate that to increase Community Satisfaction, the Dharmasraya District Health Office needs to pay attention and focus more on improving work morale and work environment.